Antioxidant, haemolytic activities and GC-MS profiling of Carissa carandas roots. - Farah Aslam; Nasir Rasool; Muhammad Riaz; Muhammad Zubair; Komal Rizwan; Mazhar Abbas; Tanveer Hussain Bukhari; Iftikhar Hussain Bukhari (International Journal of Phytomedicine, 2011)
The antioxidant potential of the plant Carissa carandas roots extracted with different polarity based solvents was assessed. The antioxidant activity was evaluated by the measurement of total phenolic contents (TPC), total flavonoid contents (TFC), reducing power, DPPH radical scavenging, IC50 and antioxidant activity in linoleic acid system. The plant material contained the TPC (1.79-4.35 GAE mg/g of dry extract), TFC (1.91-3.76 CE mg/g of dry extract), DPPH radical scavenging activity, IC50 (12.53-84.82 %) and % inhibition of peroxidation in linoleic acid (41.0-89.21 %) system respectively. Furthermore the antioxidant effectiveness of extracts was assessed using corn oil (CO) as the oxidation substrate. The oxidative alterations were evaluated by the measurement of conjugated diene (CD), conjugated triene (CT), panisidine, free fatty acid (FFA) and peroxide values (PV). The cytotoxicity of the plant extracts were assessed against human red blood cells (RBCs) and the % lysis was found to be in the range of 1.01-6.10 %. The GC-MS analysis of n-hexane extract was also profiled. It was concluded that extracts of plant roots may be used as potential source of antioxidant agents in food industries.